STEM ability perceptions, basic needs satisfaction, and intrinsic motivation in adolescents: The role of inclusive perceptions in self-determination. - Angelina Joy; Adam Hartstone-Rose; Jerica Knox; Channing J Mathews; Jacqueline Cerda-Smith; Kelly Lynn Mulvey (PLoS ONE)
Current work suggests that basic psychological needs are related to higher intrinsic motivation, which in turn, can promote more positive academic outcomes. However, few studies have examined how perceptions around one's abilities in science, engineering, technology, and math (STEM) are related to intrinsic motivation and what role needs satisfaction plays in this association. This study assessed adolescents' (N = 285, 56.1% female, Mage = 15.76 years, SD = 1.24) STEM ability perceptions, basic needs satisfaction, and intrinsic motivation. A path analysis was used to examine the association between STEM ability perceptions, basic needs satisfaction, and intrinsic motivation in adolescents. Inclusive perceptions of the STEM abilities of historically underrepresented groups (i.e., girls and minoritized ethnicities) were positively associated with basic needs satisfaction and basic needs satisfaction was positively associated with intrinsic motivation. There was also a positive indirect effect from inclusive perceptions of STEM abilities to intrinsic motivation through basic needs satisfaction. These findings suggest that schools should focus on promoting inclusive perceptions in order to bolster adolescents' basic needs satisfaction, which could have carry-on effects on intrinsic motivation.